204k views
3 votes
The graph of a line passes through the points (0, -2) and (6, 0). What is the equation of the line? y = -2x + 6 y = 13x – 6 y = 3x – 2 y = 13x – 2

User Yort
by
4.9k points

2 Answers

3 votes

Answer:


$ 2x - 3y - 6 = 0$

Explanation:

When we are to find the equation of the line passing through two points, say
$ (x_1, y_1) $ and
$ (x_2, y_2) $ we use the two -point form.

The two point form is as follows:


$ \frac{y - y_1} {y_2 - y_1} = (x - x_1)/(x_2 - x_1) $

Here,
$ (x_1 , y_1) = (0 , -2) $ and
$ (x_2, y_2) = (6 , 0) $.

Therefore we have:
$ (y + 2)/(0 + 2) = (x - 0)/(6 - 0) $


$ \implies (y + 2)/(1) = (x)/(3) $


$ \implies 3y + 6 = x $ $ \implies x -3y + 6 = 0$

User Dmitry MiksIr
by
5.6k points
4 votes

Answer:

The equation of the line is
y = (x)/(3) - 2

Explanation:

Given

Point 1 (0, -2)

Point 2 (6, 0).

Required

What is the equation of the line?

To get the equation of the line, we have to calculate the two -point form gradient formula.

Let gradient be represented by m

The expression for m is as follows;


m = (y - y_(1) )/(x - x_(1)) and


m = (y_(2) - y_(1) )/(x_(2) - x_(1))

Since m = m, we have


(y - y_(1) )/(x - x_(1)) = (y_(2) - y_(1) )/(x_(2) - x_(1))

Such that


x_(1) = 0, x_(2) = 6, y_(1) = -2, y_(2) = 0

By Substituting these values in the expression above, we'll get the equation of the line


(y - y_(1) )/(x - x_(1)) = (y_(2) - y_(1) )/(x_(2) - x_(1))

becomes


(y - (-2) )/(x - 0) = (0 - (-2) )/(6 - 0)


(y + 2 )/(x) = (0 + 2 )/(6)


(y + 2 )/(x) = (2 )/(6)


(y + 2 )/(x) = (1)/(3)

Multiply 3x to both sides


3x * (y + 2 )/(x) = (1)/(3) * 3x


3 ( {y + 2 }) = x

Open bracket


3y + 6 = x

Make y the subject of formula


3y = x - 6

Divide both sides by 3


y = (x - 6)/(3)


y = (x)/(3) - (6)/(3)


y = (x)/(3) - 2

Hence, the equation of the line is
y = (x)/(3) - 2

User GOK
by
5.5k points